Pemanfaatan Teknologi Layanan Fine Dining untuk Meningkatkan Customer Experience dan Influence Satisfaction: Utilization of Fine Dining Service Technology to Improve Customer Experience and Influence Satisfaction - Felix, Antonius; Steven Jonathan Salim; Juan Matthew Karsten; Handoko; Anlovsky; Daniel (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
The restaurant industry is a business that is popular among the public, because it promises large profit potential. One of the classifications in the restaurant industry is upscale restaurants, which are the type of restaurant that has the highest level of service. Fine dining restaurants are a type of restaurant that is included in the upscale restaurant category. Even though fine dining restaurants are included in the niche market category which has few competitors, there are quite a lot of fine dining restaurants in Jakarta & Bali. Therefore, fine dining restaurants need to present something different for their consumers. In Jakarta & Bali, a fine dining restaurant has introduced a distinctive dining experience by integrating three-dimensional visual technology and digital mapping in its Le Petit Chef program. Through the concept offered by Le Petit Chef, it provides a new touch to the culinary world, especially in Indonesia because this concept is something that has not existed before. In order to be able to face increasingly fierce competition. By providing this unique experience, researchers are interested in examining what Customer Experience factors can have an influence on Customer Satisfaction. This research aims to have an impact on customer experience at Le Petit Chef in Jakarta & Bali which involves aspects of product quality, price and service quality on the level of Customer Satisfaction. In achieving this goal, the research focus will be placed on three main aspects: (1) the influence of the impact of product quality on customer satisfaction, (2) the influence of the impact of price on the level of customer satisfaction, and (3) the influence of the impact of service quality on customer satisfaction. The approach used is a qualitative approach with descriptive and explanatory methods, utilizing secondary data. The population used in this research is all reviews on the Google Review and Tripadvisor platforms for Le Petit Chef restaurants in Jakarta & Bali, namely 115 reviews, with a sample size of 17 reviews. Sampling was carried out using the Probability sampling method. Data collection involved two sources from TripAdvisor and Google Reviews as sources to extract customer perceptions of the Le Petit Chef Jakarta & Bali restaurant. The discussion data will then be explained in more depth as to whether there are aspects such as food, price and service in the review. So that it can produce a conclusion regarding the impact of these aspects on the level of customer satisfaction. The research results show that price has a perpendicular influence on customer satisfaction, food quality that meets customer expectations has a positive impact on customer satisfaction, and service quality from a restaurant has a significant impact on customer satisfaction.